ENT300 KOOKIE / Nur Afiqah Mohamad Sa’id... [et.al] - Mohamad Sa’id, Nur Afiqah; Rejal, Nor Asyirin; Hasman, Ika Yunita; Aini, Nurhidayah (2015)
The name of our business is KOOKIE. Our business is in the form of partnership which consists of four members. Each partner contributes certain amount of capital as agreed in the partnership agreement. Every members are actively participating the business. We have reached to a consensus that Nur Afiqah binti Mohamad Sa’id is selected as the General Manager as well as the Administrative Manager, Nr Asyirin binti Rejal as the Marketing Manager, Nurhidayah Aini as the Operational Manager and Ika Yunita binti Hasman as the Financial Manager. The selection of the General Manager is based upon the agreement among the partners and is selected based on the experience, skills and ability.